2022
DOI: 10.20463/pan.2022.0010
|View full text |Cite
|
Sign up to set email alerts
|

Four weeks of lower-limb static stretching reduces regional arterial stiffness in middle-aged and older women

Abstract: [Purpose] This study aimed to clarify whether habitual lower-limb stretching intervention reduces regional arterial stiffness at the stretched site in middle-aged and older women.[Methods] In this study, the effects of 4 weeks of lower-limb static stretching (of the hip extensor and flexor, knee extensor and flexor, and plantar flexor muscles) were investigated on systemic, central, and peripheral arterial stiffness using pulse wave velocity in 14 healthy middle-aged and older women randomly assigned to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…More recent research seems to provide further evidence for this association with healthy adults with high flexibility having better arterial compliance than low-flexibility adults [19]. Furthermore, a number of training studies have found that passive stretching (a major part of the yoga session) is associated with a reduction in arterial stiffness [16,20,21].…”
Section: Comparison To the Literaturementioning
confidence: 95%
“…More recent research seems to provide further evidence for this association with healthy adults with high flexibility having better arterial compliance than low-flexibility adults [19]. Furthermore, a number of training studies have found that passive stretching (a major part of the yoga session) is associated with a reduction in arterial stiffness [16,20,21].…”
Section: Comparison To the Literaturementioning
confidence: 95%